1991
DOI: 10.1016/s0735-1097(10)80106-8
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged and fractionated right atrial electrograms during sinus rhythm in patients with paroxysmal atrial fibrillation and sick sinus node syndrome

Abstract: Intraatrial catheter mapping of the right atrium was performed during sinus rhythm in 92 patients: Group I = 43 control patients without paroxysmal atrial fibrillation or sick sinus node syndrome; Group II = 31 patients with paroxysmal atrial fibrillation but without sick sinus node syndrome; and Group III = 18 patients with both paroxysmal atrial fibrillation and sick sinus node syndrome. Atrial electrograms were recorded at 12 sites in the right atrium. The duration and number of fragmented deflections of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(111 citation statements)
references
References 17 publications
3
103
1
4
Order By: Relevance
“…14 -16 Furthermore, the recording technique applied (unipolar or bipolar recordings), mapping catheters used (type of electrodes, electrode spacing), and filter settings of the amplifiers have considerable influence on the resulting activation and voltage maps. [17][18][19][20][21][22] Most studies comparing unipolar and bipolar signals are based on animal experiments or computer simulation studies, and only a few clinical studies have been reported. [13][14][15] We evaluated the effects of the recording technique applied on voltage and activation map reconstruction in 4 groups of patients with and without CHD, using the 3D CARTO mapping system.…”
mentioning
confidence: 99%
“…14 -16 Furthermore, the recording technique applied (unipolar or bipolar recordings), mapping catheters used (type of electrodes, electrode spacing), and filter settings of the amplifiers have considerable influence on the resulting activation and voltage maps. [17][18][19][20][21][22] Most studies comparing unipolar and bipolar signals are based on animal experiments or computer simulation studies, and only a few clinical studies have been reported. [13][14][15] We evaluated the effects of the recording technique applied on voltage and activation map reconstruction in 4 groups of patients with and without CHD, using the 3D CARTO mapping system.…”
mentioning
confidence: 99%
“…18 In addition, it is now well accepted that a new and simple electrocardiographic marker, PWD, also represents inhomogeneous and discontinuous atrial conduction and has predictive value especially for paroxysmal atrial fibrillation. [19][20][21] In healthy children, P-wave duration has been reported to range from 50 to 100 ms. 22 PWD has been studied in some other cardiac conditions such as atrial enlargement, obesity, hypertension, atrial septal defect, pulmonary stenosis, and dilated cardiomyopathy. [23][24] Tükek et al 25 reported that increased sympathetic activity leads to a significant elevation in PWD.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated a strong correlation between fractionated endocardial electrograms and AF episodes 33,34 . Fragmented ventricular activation detected by endocardial electrograms has been already correlated with low-amplitude and high-frequency signals detected on body surface SAECG 35,36 .…”
Section: (B) Mec (%) (C) Sec (%) (D) Met (Hz) (E) Set (Hz)mentioning
confidence: 90%